Distinct foliar fungal communities in Pinus contorta across native and introduced ranges: evidence for context dependency of pathogen release - Ruirui Zhao; Susan J. Nuske; Martín A. Nuñez; Alex Fajardo; Jaime Moyano; Anne C. S. McIntosh; Marie-Charlotte Nilsson; Michael J. Gundale (Scientific Reports, 2025)
Abstract Inter-continental study systems are crucial for testing ecological hypotheses, such as the widely cited Enemy Release Hypothesis (ERH), which seeks to explain the superior performance of plant species when they are introduced to new regions. Pinus contorta (lodgepole pine), native to North America, has been extensively introduced to Europe and the Southern Hemisphere, making it an ideal tree species for studying invasion hypotheses from a biogeographical perspective. We compared foliar fungal communities, especially pathogens, of P. contorta across two native–introduced region pairs (NIRPs): a northern NIRP (from Canada to Sweden) and a southern NIRP (from the USA to Patagonia), while also examining the differences between source plantations and invasion fronts within Patagonia. P. contorta underwent significant fungal community shifts and experienced pathogen release during its large-scale introduction from North America to Sweden and Patagonia. The fungal richness and relative abundance changes were more pronounced for the southern NIRP pair, where no closely related tree species to P. contorta are present in Patagonia. In Sweden, the presence of the phylogenetically related P. sylvestris and its associated local fungal community appears to play a role in influencing the foliar fungal communities associated with introduced P. contorta. In Patagonia, the incomplete co-invasion of fungal taxa from the USA emerges as a principal driver of the observed variability in fungal community composition and pathogen release following the introduction of P. contorta. In Patagonia, fungal community composition differences between source plantations and invasion fronts provided insufficient evidence that pathogen release occurs at this local scale. Integrating both biogeographical and phylogenetic perspectives, our study suggests that priority effects of local fungi appear to be a dominant community assembly process when introduction is done in a phylogenetically similar community; whereas, co-invasion of fungal communities is the dominant process in phylogenetically distant communities.